2011
DOI: 10.1021/ma2017666
|View full text |Cite
|
Sign up to set email alerts
|

Structural Regularization in the Crystallization Process from the Glass or Melt of Poly(l-lactic Acid) Viewed from the Temperature-Dependent and Time-Resolved Measurements of FTIR and Wide-Angle/Small-Angle X-ray Scatterings

Abstract: INTRODUCTIONPoly(L-lactic acid) (PLLA) is now attracting many attentions because of its possibility for the practical usages as one of the general multipurposes polymer materials. However, there are many problems to be clarified including the relatively poor mechanical property, the relatively low melting point and so on. 1,2 Among these problems, the slow crystallization rate in the melt processing is one of the most serious problems in the industrial point of view. 1,2 As one important factor, the existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
129
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 56 publications
10
129
0
Order By: Relevance
“…Tashiro and co-workers reported that the isothermal crystallization of PLLA both from glassy and melt state occur through the mesophase [40]. They also reported that meltquenched PLLA is not perfectly amorphous phase, but it contains the mesophase [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tashiro and co-workers reported that the isothermal crystallization of PLLA both from glassy and melt state occur through the mesophase [40]. They also reported that meltquenched PLLA is not perfectly amorphous phase, but it contains the mesophase [40].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al showed that physically aging of glassy PLLA below the glass transition temperature (T g ) resulted in the formation of mesophase [24]. Tashiro and co-workers reported that the isothermal crystallization of PLLA both from glassy and melt state occur through the mesophase [40]. They also reported that meltquenched PLLA is not perfectly amorphous phase, but it contains the mesophase [40].…”
Section: Introductionmentioning
confidence: 99%
“…However, there was as difference in behaviour occasioned by the crystalline polymorph of PLA [14]. In case of crystallization in a'-form (also named d-form by some authors), which is a structurally less ordered crystalline form of PLA [15] obtained at crystallization temperatures lower than 100 C [16,17], no reduction of the gas permeability was obtained, even if the crystallization was carried out up to the maximum crystallinity degree [14]. When the PLA crystallization was carried out at high temperatures (>100 C) to obtain the a-polymorph, the oxygen permeability could be decreased by a factor of approximately 4 [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that melt crystallization of polymers does not occur directly from the melt to the crystalline phase, but via a pre-ordered amorphous phase named mesophase. 28,29 Mano et al 30,31 and Iannace et al 32 speculated about the existence of a rigid amorphous phase apart from the mobile amorphous phase in crystalline PLA, in which the former could be the mesophase. 28 On the other hand, melt-quenched PLA is not in a perfectly amorphous state but it forms the mesophase containing the disordered aggregation of IJ10/3) helical chain segments, which can rearrange into crystalline phase upon annealing.…”
Section: Introductionmentioning
confidence: 99%
“…The mesophase appearing in the crystallization process is formed by unoriented amorphous chains and refers to the necessary "transition state" from the amorphous to the crystalline phase, [24][25][26][27][28][29] whereas that formed in the stretching process is the strain-induced intermediate phase between the amorphous and crystalline phases, composed of highly oriented amorphous chains. The mesophase appearing in the crystallization process is formed by unoriented amorphous chains and refers to the necessary "transition state" from the amorphous to the crystalline phase, [24][25][26][27][28][29] whereas that formed in the stretching process is the strain-induced intermediate phase between the amorphous and crystalline phases, composed of highly oriented amorphous chains.…”
Section: Introductionmentioning
confidence: 99%